Given that f(x) = x2 – 3x - 10 and g(x) = x – 5, find (f - g)(x) and express
the result in standard form.

Respuesta :

Answer:

[tex](f-g)(x)= x^2-4x-5[/tex]

Step-by-step explanation:

We have the two functions:

[tex]f(x)=x^2-3x-10\text{ and } g(x)=x-5[/tex]

And we want to find (f-g)(x).

(f-g)(x) is equivalent to f(x)-g(x).

Therefore:

[tex]\begin{aligned} (f-g)(x)&=f(x)-g(x)\\ &=(x^2-3x-10)-(x-5)\end{aligned}[/tex]

Simplify:

[tex]\begin{aligned} &=x^2-3x-10-x+5 \\ &=(x^2)+(-3x-x)+(-10+5) \\ &=x^2-4x-5\end{aligned}[/tex]

Therefore:

[tex](f-g)(x)= x^2-4x-5[/tex]

Answer:

x^2 -3x+5 = 0

Step-by-step explanation: